Prose reading: The influence of text-reader factors - Revathi Gopal; Che Ton Mahmud (Universitas Syiah Kuala, 2019)
This study highlights the importance of text-reader factors in prose reading. The study was carried out to identify the text-reader factors involved in enhancing reading comprehension. A qualitative research methodology was employed involving individual in-depth interview sessions with six average ability Form Two students from a secondary school. The interviews were conducted to gauge their views on the influence of text-reader factors in text comprehension. The interview questions centered on the literature textbook currently used in school and also the short story “Cheat” by Allan Baillie included in the book. Thematic analysis was carried out on the data collected. The findings show that text-reader factors affect text comprehension. The factors include pictures, font, the author, glossary, text organization, cover of the book and the length of the literary prose forms. The reader factors are related to the students’ life background, interest, and motivation in reading. The study implies that these text-reader factors must be met to ensure improved reading comprehension ability among students.